Dynamic and Static Exercises Differentially Affect Plasma Cytokine Content in Elite Endurance- and Strength-Trained Athletes and Untrained Volunteers - Kapilevich, Leonid V.; Zakharova, Anna N.; Kabachkova, Anastasia V.; Kironenko, Tatyana A.; Orlov, Sergei N. (Frontiers in Physiology, 2017)
Extensive exercise increases the plasma content of IL-6, IL-8, IL-15, leukemia inhibitory factor (LIF), and several other cytokines via their augmented transcription in skeletal muscle cells. However, the relative impact of aerobic and resistant training interventions on cytokine production remains poorly defined. In this study, we compared effects of dynamic and static load on cytokine plasma content in elite strength- and endurance-trained athletes versus healthy untrained volunteers. The plasma cytokine content was measured before, immediately after, and 30 min post-exercise using enzyme-linked immunosorbent assay. Pedaling on a bicycle ergometer increased IL-6 and IL-8 content in the plasma of trained athletes by about 4- and 2-fold, respectively. In contrast to dynamic load, weightlifting had negligible impact on these parameters in strength exercise-trained athletes. Unlike IL-6 and IL-8, endurance exercise had no impact on IL-15 and LIF, whereas static load increases the content of these cytokines by 50%. Two-fold increment of IL-8 content seen in athletes subjected to endurance exercise was absent in untrained individuals, whereas the 50% increase in IL-15 triggered by static load in the plasma of weightlifting athletes was not registered in the control group. Thus, our results show the distinct impact of static and dynamic exercise on cytokine content in the plasma of trained athletes. They also demonstrate that both types of exercises differentially affect cytokine content in plasma of athletes and untrained persons.